Analyzing Classroom Atmosphere on the Effectiveness of English Learning - Santiara Santiara; Razali Abdullah (Universitas Serambi Mekkah, 2022)
This research was carried out to see factors that affect the classroom atmosphere on the effectiveness of English learning. It was done to investigate whether the noise, teacher factors, and classroom facilities had any effects on the effectiveness of learning English at SMP N 13 Banda Aceh. The method used in this research is a qualitative method, which is a descriptive qualitative design. Then the respondents in this study were grade 9 students at SMP N 13 Banda Aceh. The instrument used in this study was a questionnaire, it was distributed to students in order to determine the effect of the classroom atmosphere on the effectiveness of learning English. The data analysis technique used in this study is calculating the percentage. The result shows that from the3 factors, they are the noise factor of 50%, then the teachers effect is 45%, and 33% facilities affect the effectiveness of learning English in SMP N 13 Banda Aceh.